17β‐Estradiol inhibits testosterone‐induced cell proliferation in HepG2 by modulating the relative ratios of 3 estrogen receptor isoforms to the androgen receptor. Issue 10 (30th July 2018) - Xu, Zhixiang; Liu, Jun; Jianxin, Cao; Yongliang, Zhuang; Pan, Xuejun
Abstract: Sex hormones, especially 17β‐estradiol (E2) and testosterone (TEST), play crucial roles in the oncogenesis and progression of liver cancer via hormone‐related receptors. As women have a lower rate of hepatocellular carcinoma (HCC) than men, estrogens might attenuate the occurrence and development of HCC. This study aimed to investigate the inhibitory effects and mechanisms of E2 on TEST‐induced HCC development; the HepG2 cell line was used as an in vitro model. Five endpoints, including cell viability, cell apoptosis, cell cycle, receptor protein expression, and messenger RNA transcription, were investigated. Different roles and the ratios of androgen receptor (AR) and 3 estrogen receptor (ER) subtypes were also estimated. Cell viability assay showed that co‐treatment of E2 and TEST resulted in a significant inhibition of E2‐induced or TEST‐induced cell proliferation. Flow cytometry analysis revealed that combined treatment of E2 and TEST blocked the cell cycle in the G0/G1 phase as well as induced cell early apoptosis, characterized by decreased cyclin‐dependent kinase transcription and the ratio of Bcl‐2/Bax. Real‐time quantitative polymerase chain reaction and Western blot analysis results further demonstrated that estrogen receptor estrogen receptor α66 (ERα66) and estrogen receptor β (ERβ) were upregulated, whereas AR and estrogen receptor α36 (ERα36) were downregulated, irrespective of whether E2 and TEST were considered separately or together, whereas the combined treatment of E2 and TEST resulted in a decrease in the ERα66/ERβ ratio, the ERα66/ERα36 ratio, and the ERβ/ERα36 ratio, but with an increase in the ERα66/AR ratio, the ERα36/AR ratio, and the ERβ/AR ratio. To sum up, E2 could inhibit TEST‐induced cell proliferation by modulating the ratio of different hormone‐related receptors. Abstract : Both 17β‐estradiol (E2) and testosterone (TEST) promoted HepG2 cell proliferation within physiological concentrations, whereas co‐treatment with E2 and TEST significantly inhibited cell growth. Multiple factors are involved in this growth inhibition, including (a) G0/G1 cell cycle arrest, (b) early cell apoptosis induction via a decrease in the Bcl‐2/Bax ratio, and (c) a decrease in the ERα66/ERβ ratio, the ERα66/ERα36 ratio, and the ERβ/ERα36 ratio, but with an increase in the ERα66/AR ratio, the ERβ/AR ratio, and the ERα36/AR ratio.